Developing Learning Based on Learning Management System in Administration and Education Supervision Courses - Selirowangi, Nisaul Barokati; Hasbullah, Afif; Aisyah, Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to describe and test the product of learning development based on a Learning Management System (LMS). LMS is a solution to dealing with technological advances while still considering the rules contained in the learning process. LMS also can minimize the effects of time and distance that always appear in knowledge acquisition. This study uses the type of Research and Development (R&D) with the Borg and Gall model. In this study, the administrative and educational supervision courses were used as one of the first trials in implementing the LMS. Administration and academic supervision courses have been applied to all universities in Indonesia, one of which is UNISDA Lamongan. The results showed that there was a difference in better management when compared to before using the LMS. This research has implications for the importance of educators in designing their learning to achieve the goals that have been set.